Lake Pontchartrain Basin bottom sediments and related environmental resources - Manheim, Frank T.; Hayes, Laura,|d1970-; McFaul, E. J. (U.S. Dept of the Interior, U.S. Geological Survey, 2002)
Focuses on geological framework and sedimentary processes of Lake Pontchartrain Basin. Scientific Research and Assessments section features historical information on area; shipboard, field, and remote sensing studies; and a comprehensive sediment database with geological and chemical discussions of region. Multimedia Tools and Regional Resources section includes Geographic Information System (GIS) tools and data, video demonstrating vibracore sampling techniques, and abstracts from four Basics of Basin symposia